Secondary bilateral synchronization of interictal EEG discharges in focal epilepsy: prevalence and associated factors - Specktor, Polina; Spierer, Ronen; Katson, Mark; Herskovitz, Moshe (Frontiers in Neurology, 2025)
BackgroundEpilepsy is commonly categorized based on etiology, treatment, and prognosis. Misclassification can occur due to the presence of interictal secondary bilateral synchronization (SBS) discharges seen on an electroencephalogram (EEG), misleading the classification process.ObjectiveTo examine the prevalence of interictal SBS discharges in patients with focal epilepsy and to identify predictors of these discharges.DesignRetrospective analysis of patients who underwent long-term video EEG monitoring (LTVEM) from August 2001 to May 2014.MethodsWe included patients with focal epilepsy. The patients were divided into two groups based on whether or not they had SBS discharges.ResultsWe found 1,017 patients who underwent LTVEM. Of the 221 patients included in the final analysis, 36 (16%) exhibited SBS discharges. Patients in the SBS group were younger and had an earlier onset age of epilepsy. They also had higher rates of unclear seizure onset zone and focal to bilateral tonic–clonic seizures. In the binary logistic regression analysis, young onset age of epilepsy was the only significant factor.ConclusionThe prevalence of SBS discharges in focal epilepsy is relatively high (16%), emphasizing the importance of cautious interpretation of interictal EEG in epilepsy classification. Young age of disease onset is associated with higher rates of SBS.